Scientists' warning to humanity on insect extinctions. (February 2020) - Cardoso, Pedro; Barton, Philip S.; Birkhofer, Klaus; Chichorro, Filipe; Deacon, Charl; Fartmann, Thomas; Fukushima, Caroline S.; Gaigher, René; Habel, Jan C.; Hallmann, Caspar A.; Hill, Matthew J.; Hochkirch, Axel; et al.
Abstract: Here we build on the manifesto 'World Scientists' Warning to Humanity, issued by the Alliance of World Scientists. As a group of conservation biologists deeply concerned about the decline of insect populations, we here review what we know about the drivers of insect extinctions, their consequences, and how extinctions can negatively impact humanity. We are causing insect extinctions by driving habitat loss, degradation, and fragmentation, use of polluting and harmful substances, the spread of invasive species, global climate change, direct overexploitation, and co-extinction of species dependent on other species. With insect extinctions, we lose much more than species. We lose abundance and biomass of insects, diversity across space and time with consequent homogenization, large parts of the tree of life, unique ecological functions and traits, and fundamental parts of extensive networks of biotic interactions. Such losses lead to the decline of key ecosystem services on which humanity depends. From pollination and decomposition, to being resources for new medicines, habitat quality indication and many others, insects provide essential and irreplaceable services. We appeal for urgent action to close key knowledge gaps and curb insect extinctions. An investment in research programs that generate local, regional and global strategies that counter this trend is essential. Solutions are available and implementable, but urgent action is needed now to match our intentions. Highlights: We are pushing many ecosystems beyond recovery, resulting in insect extinctions. Causes are habitat loss, pollution, invasives, climate change, and overexploitation. We lose biomass, diversity, unique histories, functions, and interaction networks. Insect declines lead to loss of essential, irreplaceable services to humanity. Action to save insect species is urgent, for both ecosystems and human survival.